UJI AKTIVITAS ANTIOKSIDAN FRAKSI ETIL ASETAT DAUN KARET KEBO (Ficus elastica) DENGAN MENGGUNAKAN METODE FRAP - Hasyim, Amita; Suhaenah, Asriani; Tahir, Masdiana (PHARMACY UMI JOURNAL SYSTEM, 2023)
Free radicals are atoms, molecules or compounds that can stand alone, having one or more unpaired electrons in their outermost orbitals. Antioxidants are molecules that are able to deactivate or stabilize free radicals. The kebo rubber leaf plant is known to have benefits as an antioxidant because it contains ingredients such as glycosides, flavonoids, phenolic acids, alkaloids, steroids, saponins, coumarins, tannins, and triterpenoids. The aim of this research was to test the antioxidant activity of the ethyl acetate fraction of kebo rubber leaves (Ficus elatica) using the FRAP (Ferric Reducing Antioxidant Power) method. The rubber kebo leaf extraction method uses the maceration method with 96% ethanol solvent. The ethanol extract was fractionated using the liquid-liquid partition method to obtain the ethyl acetate fraction. the sample fraction was added with several FRAP reagents and then measured using a UV-Vis spectrophotometer at a maximum wavelength of 712 nm with quercetin as a comparison. The results showed that the ethyl acetate fraction of kebo rubber leaves for antioxidant activity was 26.692 mgQE/g fraction.